Alteridad e identidad. Los jesuitas en Constantinopla en el s. XVIII - Marín Riveros, José (Byzantion Nea Hellás, 2015)
Otherness and identity. This work deals with such historie problems, specifically with the case of the Jesuits missionaries in Constantinople during the first half of the 18th century. Our specific interest is the study of the otherness and identity relationships between those missionaries and the muslims. We try to demonstrate that the essential characteristic of those relationships is an intransigent otherness – of an unilateral character–, but tolerant. This situation can be explained from two points of view: a political one and a religious one.Our study has its basis mainly in the study of the sources, which, in this case, are the letters-reports sent by the Jesuits missionaries to their superiors in France. Those letters-reports deal with the progress of the Constantinople mission.